The Cobalamin-Dependent Gene Cluster of Listeria monocytogenes: Implications for Virulence, Stress Response, and Food Safety - Anast, Justin M.; Bobik, Thomas A.; Schmitz-Esser, Stephan (Frontiers in Microbiology, 2020)
Several genes of the eut, pdu, and cob/cbi operons are responsible for the metabolism of ethanolamine and 1,2-propanediol and are essential during the pathogenic lifecycles of various enteric pathogens. Studies concerning ethanolamine and 1,2-propanediol metabolism have primarily focused on bacterial genera from the family Enterobacteriaceae, especially the genus Salmonella. Listeria monocytogenes is a member of the Firmicutes phylum and is the causative agent of the rare but highly fatal foodborne disease listeriosis. The eut, pdu, and cob/cbi operons are organized as a single large locus collectively referred to as the cobalamin-dependent gene cluster. The cobalamin-dependent gene cluster is well conserved in Listeria monocytogenes; however, functional characterization of the genes in this cluster and how they may contribute to Listeria virulence and stress tolerance in food production environments is highly limited. Previous work suggests that the degradation pathway of 1,2-propanediol is essential for L. monocytogenes establishment in the gastrointestinal tract. In contrast, ethanolamine metabolism may be more important during intracellular replication. Other studies indicate that the cobalamin-dependent gene cluster is utilized when Listeria monocytogenes is exposed to food and food production relevant stress conditions. Perhaps most noteworthy, Listeria monocytogenes exhibited attenuated growth at cold temperatures when key ethanolamine utilization pathway genes were deleted. This review aims to summarize the current knowledge of these pathways in Listeria monocytogenes and their significance in virulence and stress tolerance, especially considering recent developments.